The Community Justice Strategies for Crime Protection at Bansadet Sub-district, Kiansa District, Surat Thani Province - Chaiyapong, Akkakorn; Weerakul, Supatchaya (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
This research aims to examine the operation of community’s justice network in preventing crime, investigate collaboration in community’s justice network, and determine the strategy of community’s justice network to prevent crime. The research applied mixed methods design, including qualitative research, in-depth interview, focus group, and quantitative research. The data were collected using questionnaire. Population and samples include 9 experts, 6 community’s justice network staffs, members of community’s justice network, and relevant officers, accounted 200 person’s altogether. The samples were specifically selected. Research tools include in-depth interview and questionnaire. Data analysis were conducted using descriptive statistics, frequency, and percentage. The results revealed that: (1) the operation of community’s justice network consists of understanding, encouraging community members to collectively solve the problems, having crime prevention principle, having surveillance role, collectively thinking about solutions and sharing opinions. (2) Participation in preventing crime: It was found that they have good cooperation. They work with officers and related agencies to prevent crime. However, there are some problems with certain agencies and (3) Strategy of community’s justice network for preventing crime must be adapted regarding its ideas and legal strategy. It requires budget support, personnel development, and support from relevant agencies. Furthermore, there should be training about legal regulations, assigning patrol officers to reach out and listen to the community’s problems. There should be clear operation plan for preventing crime.